Backpacker Rohani: An Effort to Cultivate Moderate Insights Based on Islamic Religious Education Teaching Materials - Aba Agil Aziz; Khairul Rifa’i (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
The learning process requires teaching materials that are useful for making it easier for educators to convey information on teaching materials in the form of materials. The development of teaching materials is needed in order to support learning needs. This study describes the development of spiritual backpacker-based teaching materials as an effort to inculcate the value of religious moderation. The research process is field research using a phenomenological approach. MI Alam Alfa Kids was used as the research location to collect concrete data. sources of data in the form of interviews, observations, and documentation as the main data. The analysis was carried out by presenting data, reducing it, and concluding. The results of this study are: 1) the development of spiritual backpacker-based teaching materials is the development of teaching materials that are adapted to the learning designs at MI Alam Alfa Kids, namely spiritual backpacker-based learning as an effort to instill the value of religious moderation; 2) Spiritual backpacker teaching materials give participants firsthand experiences of being directly connected to the community environment, giving them open insight into how to be moderate. 3) Teaching materials have advantages, including an integrated learning process with the environment, fostering student inquiry, and training students to live tolerantly in community. The drawbacks of this model are that not all subjects can be developed using it; it requires special time; not all ages can apply spiritual backpacker-based teaching materials; and the implementation of teaching materials must be accompanied by more than one teacher.